Analisis Kepemimpinan Pendidikan Islam Dalam Konsep Pendidikan Holistik - Istiqamah; Jonny; Khafiyya Ramadhini; Almahfuz (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the integration of Islamic educational leadership with the concept of holistic education as a response to the challenges of 21st-century education. Employing a qualitative approach through library research and thematic analysis based on Braun and Clarke’s model, the study focuses on three key areas: first, spirituality as the foundation of Islamic leadership, grounded in values such as amanah, khalifah, ikhlas, tawakal, and muraqabah; second, the identification of integrative principles—tawazun, tawhid, rahmah, adl, and ihsan—which align with holistic education principles; and third, the formulation of a transformational-spiritual leadership model built on four pillars: spiritual, intellectual, emotional, and social, along with its implementation strategies through curriculum transformation, leadership capacity development, and organizational culture building. The findings demonstrate that integrating Islamic values with holistic educational principles not only enriches leadership theory but also offers a practical framework applicable to contemporary Islamic educational institutions in a contextual and sustainable manner.